Crisis Navigation in the Era of Disruption: An Exploration of Situational Crisis Communication Theory (SCCT) Strategies in Public Relations of the West Java Provincial DPRD - Machsunah, Uun; P, Triyuda; Novita, Lisna (ann4publisher@gmail.com, 2026)
Background. Public communication in the legislature faces increasingly complex challenges amid massive digital disruption. The phenomenon of post-truth and the speed of information virality often puts institutions such as the West Java Provincial Parliament in a difficult-to-predict reputation crisis. Aims. This research analyzes the crisis communication strategy of the West Java Provincial DPRD Public Relations in mitigating adverse reporting regarding budget issues in the digital disruption era. By integrating Situational Crisis Communication Theory (SCCT) and SWOT analysis, this study explores how institutional reputation is maintained through strategic digital platforms. Methods. Using a qualitative descriptive method with purposive sampling, data were collected through in-depth interviews, observation, and documentation. Result. The results indicate that the DPRD Public Relations employs a combination of Diminish and Bolstering strategies. The SWOT analysis results, with coordinates (0.27; 0.43), place the institution in the aggressive-growth quadrant, underscoring the importance of integrating social media as a technical tool for rapid clarification. This study reinforces previous methodological findings on the urgency of SWOT analysis for mapping organizational resilience. Conclusion. The research concludes that navigating crises in the disruption era requires synchronizing technical digital agility with a unified internal narrative across political factions. Implementation. In practice, this research underscores the need to establish internal regulations, in the form of an SOP on Crisis Communication Across Factions, to ensure a single voice in responding to public issues. Academically, this study strengthens the relevance of integrating SWOT analysis into SCCT theory for legislative institutions in the era of disruption.